P53 protein accumulation predicts malignant progression in Barrett's metaplasia: a prospective study of 275 patients. Issue 1 (11th April 2017) - Younes, Mamoun; Brown, Keith; Lauwers, Gregory Y; Ergun, Gulchin; Meriano, Frank; Schmulen, A Carl; Barroso, Alberto; Ertan, Atilla
Abstract : Aims: The purpose of this study was to determine prospectively whether p53 protein accumulation in biopsies of Barrett's metaplasia (BM) is a predictor of malignant progression, without relying on dysplasia grading. Methods and results: Sections of formalin‐fixed paraffin‐embedded tissue from the initial biopsies of 275 patients with BM, who had no high‐grade dysplasia (HGD) or oesophageal adenocarcinoma (EAC), were stained for p53 by immunohistochemistry. The mean follow‐up was 41 months. p53‐positive biopsies were divided into four groups: scattered positive cells, multifocal scattered positive cells, aggregates of positive cells, and multifocal aggregates of positive cells. Kaplan–Meier analysis with the log‐rank test was used to determine the rate of progression to HGD/EAC. Of the 275 patients, 227 had initial biopsies that were completely negative for p53, and, of these, one (0.4%) progressed to HGD/EAC; none of 24 (0%) patients with scattered positive cells and none of four (0%) of patients with multifocal scattered positive cells progressed. In contrast, five of 16 (31.25%) patients with aggregates of positive cells and three of four (75%) of those with multifocal aggregates of positive cells progressed to HGD/EAC. Kaplan–Meier analysis with log‐rank statistics showed the difference in progression rate between the five groups to be highly significant ( P < 0.0001). Conclusions: We conclude that p53 protein accumulation, detected by immunohistochemistry in aggregates of cells, is a significant predictor of malignant progression in patients with BM.